Mre11-Rad50 promotes rapid repair of DNA damage in the polyploid archaeon Haloferax volcanii by restraining homologous recombination. - Stéphane Delmas; Lee Shunburne; Hien-Ping Ngo; Thorsten Allers (PLoS Genetics)
Polyploidy is frequent in nature and is a hallmark of cancer cells, but little is known about the strategy of DNA repair in polyploid organisms. We have studied DNA repair in the polyploid archaeon Haloferax volcanii, which contains up to 20 genome copies. We have focused on the role of Mre11 and Rad50 proteins, which are found in all domains of life and which form a complex that binds to and coordinates the repair of DNA double-strand breaks (DSBs). Surprisingly, mre11 rad50 mutants are more resistant to DNA damage than the wild-type. However, wild-type cells recover faster from DNA damage, and pulsed-field gel electrophoresis shows that DNA double-strand breaks are repaired more slowly in mre11 rad50 mutants. Using a plasmid repair assay, we show that wild-type and mre11 rad50 cells use different strategies of DSB repair. In the wild-type, Mre11-Rad50 appears to prevent the repair of DSBs by homologous recombination (HR), allowing microhomology-mediated end-joining to act as the primary repair pathway. However, genetic analysis of recombination-defective radA mutants suggests that DNA repair in wild-type cells ultimately requires HR, therefore Mre11-Rad50 merely delays this mode of repair. In polyploid organisms, DSB repair by HR is potentially hazardous, since each DNA end will have multiple partners. We show that in the polyploid archaeon H. volcanii the repair of DSBs by HR is restrained by Mre11-Rad50. The unrestrained use of HR in mre11 rad50 mutants enhances cell survival but leads to slow recovery from DNA damage, presumably due to difficulties in the resolution of DNA repair intermediates. Our results suggest that recombination might be similarly repressed in other polyploid organisms and at repetitive sequences in haploid and diploid species.